Volleyball and access to political power: Afro-Peruvian congresswomen - Gonzales, Sharún (2020)
Since 2000, women recognized as Afro-Peruvians have always been present at the Peruvian Congress. This fact distinguishes Peru from other countries in the region where Afro-descendant women are widely absent. On the other hand, Afro-Peruvian women included as representatives share characte-ristics such as their origins in families unrelated to politics and an outstanding career as professional volleyball players. Through semi-structured interviews with women identified as Afro-Peruvian who were elected to the Congress of the Republic of Peru this article explores their routes to political power from an intersectional perspective. Instead of the traditional path to power through family ties or the paths of political and community activism, participants in this study exemplify an alternative route to being elected representatives: volleyball. This relationship, however, occurs amid paradoxes between the exclusion and inclusion of Afro-Peruvian women in general.